BAHAN BAKAR CAIR DARI LIMBAH PLASTIK DENGAN METODE CATALYTIC CRACKING - renilaili, renilaili (Jurnal Tekno, 2019)
Indonesia with a very large population, is currently working hard to diversify its energy, in order to meet energy needs in the country, especially electricity and fuel energy, preferably environmentally friendly renewable energy, when this plastic waste becomes national problems because they cannot decompose under ordinary conditions unless they are converted into chemical fuel. This study aims to obtain liquid fuel energy, in this case used HDPE plastic waste raw material (in the form of packaged drinking water), this plastic waste is processed using the Catalitic Cracking method with silica Alumina as a catalyst, the process lasts for 4 hours with a temperature of 100 -400oC and 53% of the plastic oil obtained, brownish yellow, with density and viscosity and flash point approaching kerosine compounds to diesel fuel, in the process of catalytic cracking, temperature factors, process length and the catalyst used greatly affect the number of products and product quality from the liquid fuel produced.